Urgensi Revisi Peraturan tentang Tindak Pidana Ringan dalam Hukum Kesehatan di Era Pandemi - Karman Karman (Jurnal Kesehatan, 2024)
The global COVID-19 pandemic has presented unprecedented challenges to health systems around the world, including Indonesia. In this context, health-related law enforcement has become increasingly crucial. This paper discusses the urgency of revising regulations on minor criminal offences in health law in the pandemic era. This research uses a qualitative method with a descriptive-analytical approach, focusing on analysing the prevailing laws and regulations, the implementation of law enforcement, and its impact in public health emergency situations. Revisions to health law regulations need to be made to adjust to the dynamics of the pandemic and the protection of public health. The mismatch of existing regulations may hinder quick and effective response to health-related offences. These changes are expected to strengthen the legal framework, provide legal certainty, and improve public compliance with health protocols. Finally, this study provides recommendations for policymakers on concrete steps that need to be taken to optimise health law enforcement in pandemic emergencies.